Host community similarity and geography shape the diversity and distribution of haemosporidian parasites in Amazonian birds. Issue 3 (12th May 2017) - Fecchio, A.; Pinheiro, R.; Felix, G.; Faria, I. P.; Pinho, J. B.; Lacorte, G. A.; Braga, E. M.; Farias, I. P.; Aleixo, A.; Tkach, V. V.; Collins, M. D.; Bell, J. A.; et al.
Abstract : Identifying the mechanisms driving the distribution and diversity of parasitic organisms and characterizing the structure of parasite assemblages are critical to understanding host–parasite evolution, community dynamics, and disease transmission risk. Haemosporidian parasites of the genera Plasmodium and Haemoproteus are a diverse and cosmopolitan group of bird pathogens. Despite their global distribution, the ecological and historical factors shaping the diversity and distribution of these protozoan parasites across avian communities and geographic regions remain unclear. Here we used a region of the mitochondrial cytochrome b gene to characterize the diversity, biogeographical patterns, and phylogenetic relationships of Plasmodium and Haemoproteus infecting Amazonian birds. Specifically, we asked whether, and how, host community similarity and geography (latitude and area of endemism) structure parasite assemblages across 15 avian communities in the Amazon Basin. We identified 265 lineages of haemosporidians recovered from 2661 sampled birds from 330 species. Infection prevalence varied widely among host species, avian communities, areas of endemism, and latitude. Composition analysis demonstrated that both malarial parasites and host communities differed across areas of endemism and as a function of latitude. Thus, areas with similar avian community composition were similar in their parasite communities. Our analyses, within a regional biogeographic context, imply that host switching is the main event promoting diversification in malarial parasites. Although dispersal of haemosporidian parasites was constrained across six areas of endemism, these pathogens are not dispersal‐limited among communities within the same area of endemism. Our findings indicate that the distribution of malarial parasites in Amazonian birds is largely dependent on local ecological conditions and host evolutionary relationships.